Implementation of IPv6 Protocol in EIGRP Routing to Improve Data Transfer Efficiency in Wide Area Networks - Dewantara, Yudhistira (Journal of Technology and Computer, 2025)
The development of network technology has encouraged the adoption of Internet Protocol version 6 (IPv6) as a solution to the limitations of IPv4, especially in terms of address space and network efficiency. Consequently, a routing protocol capable of optimally supporting the complexity of IPv6 networks is required. Enhanced Interior Gateway Routing Protocol (EIGRP) is a dynamic routing protocol that natively supports IPv6 and is known for its efficiency and scalability. This study aims to examine the implementation of EIGRP on IPv6 networks, specifically in improving data transfer efficiency on Wide Area Networks (WANs). Testing was conducted using Cisco Packet Tracer, with evaluations of device connections, latency performance, and routing paths. The test results showed good connectivity between devices, with an average latency value of 0.5 ms, as well as an optimal routing path based on the Diffusing Update Algorithm (DUAL) algorithm. Configuration adjustments such as the Autonomous System (AS) value and K-value were proven to affect routing efficiency. This study concludes that EIGRP on IPv6 is able to improve data delivery efficiency and is a reliable solution in modern network development. These results can be a reference for network developers in optimizing IPv6 routing configurations.